Estudo do modelado atual da paisagem da cidade de Pacaraima-RR a partir da análise da ação antrópica e feições erosivas - Caicedo Marquez, Javier Antonio (2018)
The landscape of the urban area of the city of Pacaraima and surroundings located on the Pacaraima sierra, presents a great diversity of geomorphological features formed by hills with levels in structured crests, hills and hills with open valleys where small plains are located intermontane. This singular configuration of the Landscape has been appropriated by men, who by modifying the natural geomorphology of the relief changes the natural balance of the environment, interfering in the morphodynamic processes. Thus, this research has as main objective, to analyze the modeling of the current landscape of the city from the analysis of the anthropic action and the erosive features. As a help in landscape analysis, photo interpretative techniques were used in remote sensing images, which allowed the development of digital terrain models (altimetry and slope) and topographic profiles for the characterization of relief forms. The bibliographical and field research was used as a methodological approach. Field activities, based on empirical observation, were carried out in order to: characterize morphologically (morphography and morphometry) the relief forms; to identify anthropogenic interventions that modify the natural morphology of relief; identify and characterize the erosive features located in the city of Pacaraima. Thus, the geomorphological compartments are established by surfaces that can reach 1000 meters, like the elephant's residual hill in the north. The lower levels were identified to the northeast in the district from the balance with altitude that reach 900m. While the slope, it was observed that the urban spot of Pacaraima has already occupied the areas of low slope reliefs (flat to gently undulating), in contrast to the areas of greater slope (Rippled to strong wavy) that has been the target of irregular occupations. This fact obliges the execution of earthworks and cuts in the slopes to make these reliefs with strong slopes in areas for the occupation, thus promoting the silting of the courses, formation of groove and ravines that can evolve to gullies. It was possible to verify in terms of environmental damages by the appearance of gullies, such as the loss of usable area (7,000 m2) and soil loss (35,000 m3).